Transition of vortex pinning behaviour induced by an artificial microstructure design in Ba(Fe0.94Co0.06)2As2 pnictide superconductor. (October 2022) - Tang, M.H.; Dong, C.H.; Xu, Z.T.; Liu, C.; Yang, P.; Tu, C.; Guo, W.W.; Zhu, Y.C.; Yao, C.; Huang, H.; Wang, D.L.; Zhang, X.P.; et al.
Abstract: Among various systems of iron-based superconductors, the doped Ba122 polycrystals have shown the largest application value because of their brilliant properties and chemical stability. Since there have been few reports on the vortex dynamics in Ba122 polycrystal, we firstly conduct a comparative investigation on the differences of vortex dynamics in Ba(Fe0 . 94 Co0.06 )2 As2 single crystal, grain oriented polycrystal and random oriented powder in this paper. Herein, the polycrystal, which has c-axis grain texture, is prepared by the compaction of designed single crystal powder. The second magnetization peak (SMP) effects are observed in the hysteresis loops of single crystal and totally disappear in those of polycrystal and powder. Conventional magnetization relaxation and Maley's method are applied to analyse the vortex dynamics. In single crystal, the SMP effect is primarily related to the crossover of elastic-plastic vortex creep. The weak pinning in single vortex regime results in large magnetization relaxation rates ( S ) in low magnetic field regime. In polycrystal for H //AD (axial direction), the introduction of strong pins is effective to single vortex pinning, which brings about much lower S values in low magnetic field regime. Furthermore, the results of single crystal for H //ab, polycrystal for H //RD (radial direction) and random oriented powder are analyzed. Synergistic effects of strong pins and microscopic anisotropy on the vortex dynamics are discussed. These results will provide new knowledge for the design of high-performance Ba122 superconductors. Graphical abstract: Image 1 Highlights: Providing a new method of preparing c-axis oriented polycrystalline superconductors. Comparisons on Ba122 single crystal, oriented polycrystal and unoriented powder. Synergistic effects of strong pins and anisotropy on vortex creep are discussed。.